Analyzes of the ICF Domain of Activity After a Neurological Early Mobility Protocol in a Public Hospital in Brazil - Lima, Fernanda dos Santos; Carvalho, Vinícius da Silva; Bittencourt, Inaiacy Souto; Fontana, Ana Paula (Frontiers in Rehabilitation Sciences, 2022)
Background: Early Mobilization has been recognized as a feasible and safe intervention that improves functional outcomes in hospitalized patients. The International Classification of Functioning, Disability and Health (ICF) supports understanding of functioning and disability in multidimensional concepts. However, ICF is poorly explored to classify activities in hospital environment, especially using ICF performance qualifiers in the activity domain. Objective: To compare ICF permormance qualifier in two time points: before and after the implementation of a Neurological Early Mobility Protocol (NEMP) in intermediate care settings. Design: an interventional and longitudinal study. Methods: NEMP was used to improve patients` activity level during hospital stay in neurological wards settings. The Hospitalized Patient Mobility Questionnaire (HPMQ) identified patients` need of assistance during the performance of some hospital activites, which were transposed to ICF performance qualifiers through generic scale. Modified Barthel Index (MBI) also was re-coded to ICF and both activities assessments were applied in the first and last sessions of NEMP. The Wilcoxon Signed Rank Test compared data form these scalesin these two time points. Results: Fifty-two patients were included with median (minimum, maximum) age of 58 (16, 94) years and length of hospital stay of 25 (6, 89) days. Data collected with HPMQ revealed progressions for all activities (p < 0.001), as well as the improvements observed in ICF performance qualifiers, as bathing changingfrom d5108.3 (severe difficulty) to d5108.1 (mild difficulty), for example. A functional progression average of 36 (0-100) to 52 (0-100) points was observed using MBI (p<0.001). Limitations: The delay in initiating NEMP compared to the period observed in literature. The study was carried out at only one center. Conclusions: This study suggests that neurological inpatients, in a public hospital in Brazil, had low patterns of activity as seen in the ICF performance qualifier. However, improvements in ICF activity domain were found after NEMP even initiating after 72 hours from hospital admission.